The impact of supply chain collaboration on performance in automotive industry: Empirical evidence - Jamal Ahmed Al-Doori (Journal of Industrial Engineering and Management (JIEM), 2019)
Purpose: Indeed due to global advancement, rapid technological innovation, and enhancing regional influence, supply chain (SC) has become an essential element. Now, competition has shifted from organization to industry level; any disruption can not only disturb organization but also affect the whole industry. Although Pakistan is agriculture land still industry sector is supporting more than half population, especially the automotive sector is the highest growing sector. Due to regional and economic shift toward China and India, this sector is facing numerous problems. Only thirteen large-scale automotive organizations are operational by creating collaboration among them many issues can be resolved. Supply chain collaboration has dogged the performance in various industries and in various regions. The aim of this study is to explore the potential benefits of supply chain collaboration toward achieving operational performance. Design/methodology/approach: This is an empirical investigation conducting among supply chain department of automotive industries in Pakistan. Data were collected from 232 members of the supply chain that include suppliers, manufacturers, and distributors. Factor analysis and multiple regressions through SPSS have been used for data analysis. Findings: The finding of this study reveals that two supply chain management approaches information sharing (IS), joint decision making (JDM) significantly effect, while Electronic Data Interchange (EDI) does not have a significant effect on operational performance. Research limitations: This study consists only three approaches, next study should include more approaches. Secondly, this study is limited to the automotive sector. Practical implications: [This study will help the managers of the automotive industry in making their operation smooth by applying information sharing, joint decision making, and electronic data interchange. Originality/value: First novelty of this study is the implementation of supply chain collaboration for developing country especially for Pakistan. Secondly, this study seed collaboration as communication and include all aspects of communication like formal communication, informal communication.
Keywords: 650; Supply chain; supply chain collaboration; operational performance